LINGUISTIC AND STYLISTIC FEATURES OF PUBLICISTIC TEXTS FOR CHILDREN (BASED ON THE GERMAN LANGUAGE) - N.P. Merzlyakova (Многоязычие в образовательном пространстве, 2024)
The paper examines the linguistic and stylistic features of news style for children in German. The aim of the research is to study the linguistic specifics of news style in the texts of Internet media intended for children. The study of the peculiarities of journalism aimed at children is relevant due to the importance of the object of study itself for the development of critical thinking and cognitive interest in children, as well as for their socialisation. There are virtually no studies of this kind at present, which also confirms the relevance and novelty of the work. Theoretical significance lies in the clarification of the characteristics of the news style for a separate target group. The research material and its results have practical significance for the course of stylistics and teaching German in general. The material of the study presents German texts obtained from three news sites for children. The main research methods are the methods of linguostylistic and contextual analysis. The conducted research allowed to identify and describe some common features of the news texts for adults and children. The linguostylistic specifics of news texts for children include: enumeration (often with a hyperonym or introductory words with the meaning “for example”), questions used as headines, personal and possessive pronouns of the first and second person. Abbreviations are supplemented by decoding or a hyperonym. In addition to a large number of words with a specific meaning, the words with a generalised meaning are often found. The composition and speech form “explanation” prevails, it may include specific pronouns, adjectives and conjunctions, verbs with the meaning “to denote, to be called,” definitions of terms, comments on the pronunciation of foreign words, listing examples.